Developing a regional strategy to address the outbreak of banana Xanthomonas wilt in East and Central Africa: Proceedings of the banana Xanthomonas wilt regional preparedness and strategy development workshop held in Kampala, Uganda, 14-18 February 2005 - Karamura, E.B.; Osiru, M.; Blomme, Guy; Lusty, Charlotte E.; Picq, C. (2006)
Proceedings of a workshop to develop a coherent regional and international response for containing the spread of banana Xanthomonas wilt in East and Central Africa and mitigating its impact on rural livelihoods.